(untitled) (Jurnal Desain Komunikasi Visual Nirmana, 2011)
Cartoon as a medium has made visualization one of most important points in transmitting messages as texts, whether verbal or visual, as a process of communication that generates meanings. The “bluetooth handsfree” version of Benny & Mice cartoons is a visual discourse filled with signs. Besides images, signs of texts also determine the direction of the problem. From analyzing visual images in Benny & Mice cartoons using denotative and connotative semiotic analysis, they are interpreted that the city’s poor citizens living in Jakarta are up to date with the lifestyle trends of big cities, even though their conditions are far from it.